Anti-aging environment-friendly waterproof asphalt as well as preparation method and application thereof

By using concave and convex rod soil-loaded copper oxide modified 9,10-dihydro-9-oxa-10-phosphate-10-oxide as additives in waterproof asphalt, the problems of poor anti-aging performance and harmful gas emissions in the prior art have been solved, and higher aging resistance and environmental protection are achieved.

CN119684810APending Publication Date: 2025-03-25WUHAN UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411860514.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The lack of special asphalt in the prior art makes it difficult to control the product quality of polymer-modified asphalt waterproof coils, poor anti-aging performance, and harmful gases will be emitted during production and construction.

Method used

Asphalt and catalytic cracked oil slurry are used as basic raw materials, combined with the concave and convex rod soil-loaded copper oxide modified 9,10-dihydro-9-oxa-10-phosphate-10-oxide as an aging-resistant environmentally friendly additive, which significantly improves the aging resistance and environmental protection of waterproof asphalt and reduces harmful gas emissions.

Benefits of technology

It significantly improves the aging resistance and environmental protection of waterproof asphalt, extends the service life of waterproof rolls, and reduces the emission of harmful gases during production and construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005193092870000061
    Figure BDA0005193092870000061
  • Figure BDA0005193092870000071
    Figure BDA0005193092870000071
  • Figure BDA0005193092870000091
    Figure BDA0005193092870000091
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and discloses anti-aging environment-friendly waterproof asphalt as well as a preparation method and application thereof. The anti-aging environment-friendly waterproof asphalt is prepared from the following raw materials in parts by mass: 30 to 50 parts of asphalt, 50 to 70 parts of catalytic cracking slurry oil and 0.5 to 2.5 parts of attapulgite loaded copper oxide modified 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. The asphalt and the catalytic cracking oil slurry are used as basic raw materials, and the attapulgite-loaded copper oxide modified 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is used as an anti-aging environment-friendly additive, so that the aging resistance and the environmental protection property of the waterproof asphalt are remarkably improved, the emission of harmful gases in the production and construction processes of the waterproof coiled material can be greatly reduced, and the production cost is reduced. And the service life of the waterproof roll is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to an aging-resistant, environmentally friendly, waterproof asphalt and a preparation method and application thereof. Background Art

[0002] Polymer modified asphalt waterproofing membrane has always been a dominant material in my country due to its excellent high and low temperature performance, waterproof performance and construction performance. Asphalt is the main raw material for preparing polymer modified asphalt waterproofing membrane, and its quality is extremely critical to the performance of waterproofing membrane.

[0003] At present, my country lacks special asphalt for producing polymer modified asphalt waterproofing membranes. Generally, No. 70 or No. 90 road asphalt is used as raw material and a certain amount of softening oil is mixed to improve the low-temperature performance of waterproofing membranes. However, the product quality is difficult to control and the product anti-aging performance is poor. Therefore, the development of waterproof asphalt is extremely important for improving the quality of waterproofing membranes and extending the service life of waterproofing materials. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide an aging-resistant and environmentally friendly waterproof asphalt and a preparation method and application thereof in view of the deficiencies in the prior art. Asphalt and catalytic cracking oil slurry (FCC oil slurry) are used as basic raw materials, and attapulgite-loaded copper oxide (CuO)-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is used as an aging-resistant and environmentally friendly additive, which significantly improves the aging resistance and environmental protection of the waterproof asphalt, reduces the emission of harmful gases during the production and construction of waterproof membranes, and extends the service life of the waterproof membranes.

[0005] In order to solve the technical problem raised by the present invention, the present invention provides an aging-resistant, environmentally friendly and waterproof asphalt, comprising the following raw materials in parts by weight: 30 to 60 parts of asphalt, 40 to 70 parts of catalytic cracking oil slurry, and 0.5 to 2.5 parts of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0006] Preferably, the aging-resistant, environmentally friendly and waterproof asphalt comprises the following raw materials in parts by weight: 40 to 50 parts of asphalt, 50 to 60 parts of catalytic cracking oil slurry, and 1.0 to 2.0 parts of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0007] In the above scheme, the asphalt is road petroleum asphalt, with a softening point of 45-50°C and a needle penetration of 60-80 dmm at 25°C.

[0008] In the above scheme, the catalytic cracking slurry is the bottom oil produced in the production process of the heavy oil catalytic cracking unit, and its solidification point is 15-25°C and its density is 1.03-1.07 g / cm3 The saturated content is 20-30%, and the aromatic content is 50-65%.

[0009] In the above scheme, the preparation method of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide comprises the following steps:

[0010] 1) adding attapulgite to hydrochloric acid, stirring and drying the obtained solid to obtain acid-treated attapulgite;

[0011] 2) adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and acid-treated attapulgite into anhydrous ethanol, heating and stirring to react, and drying the obtained solid to obtain attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide;

[0012] 3) After copper nitrate is dissolved in water, the pH is adjusted with a sodium hydroxide solution, and then attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added, and after stirring for reaction, the obtained solid is dried to obtain attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0013] Furthermore, the particle size of the attapulgite is 200 to 1000 meshes.

[0014] Furthermore, the concentration of the hydrochloric acid is 0.5 to 1 mol / L.

[0015] Furthermore, the mass ratio of the attapulgite to the volume of hydrochloric acid is 1 g: (5-10) mL.

[0016] Furthermore, in step 1), the stirring speed of the stirring treatment is 100 to 200 r / min, and the treatment time is 10 to 30 min.

[0017] Furthermore, in step 1), step 2) and step 3), the drying temperature is 100-110° C. and the drying time is 1-2 hours.

[0018] Furthermore, the particle size of the acid-treated attapulgite is 200 to 1000 meshes.

[0019] Furthermore, in step 2) and step 3), the weight proportions of the raw materials are: 5 to 20 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 70 to 90 parts of acid-treated attapulgite, and 5 to 10 parts of copper nitrate.

[0020] Furthermore, the mass ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the volume ratio of anhydrous ethanol is 1 g: (8-10) mL.

[0021] Furthermore, in step 2), the stirring speed of the temperature-raising stirring reaction is 100 to 300 r / min, the reaction temperature is 50 to 60° C., and the reaction time is 30 to 60 min.

[0022] Furthermore, the particle size of the attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 200 to 1000 meshes.

[0023] Furthermore, the volume ratio of the copper nitrate to water is 1 g: (10-20) mL.

[0024] Furthermore, the concentration of the sodium hydroxide solution is 0.5-1 mol / L, and the pH is adjusted to 5-5.5.

[0025] Furthermore, in step 3), the stirring speed of the stirring reaction is 100 to 300 r / min, and the reaction time is 20 to 30 min.

[0026] Furthermore, the particle size of the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 200 to 1000 meshes.

[0027] The present invention also provides a method for preparing aging-resistant and environmentally friendly waterproof asphalt, comprising the following steps:

[0028] The asphalt is heated to a molten state and then added to a modification tank. The temperature is raised to a preset temperature and then kept warm. Catalytic cracking oil slurry is first added for stirring once, and then attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added and stirred for a second time to obtain aging-resistant, environmentally friendly and waterproof asphalt.

[0029] In the above solution, the preset temperature is 120-150°C.

[0030] In the above scheme, the stirring rate of the primary stirring is 300-500 r / min, and the stirring time is 15-20 min.

[0031] In the above scheme, the stirring rate of the secondary stirring is 300-500 r / min, and the stirring time is 30-60 min.

[0032] In the above scheme, the softening point of the aging-resistant and environmentally friendly waterproof asphalt is 25 to 35°C, the needle penetration at 25°C is 200 to 400 dmm, and the low-temperature flexibility is -2 to -10°C.

[0033] The present invention also provides an application of aging-resistant and environment-friendly waterproof asphalt in polymer-modified asphalt waterproof coiled material.

[0034] In the above scheme, the aging-resistant and environmentally friendly waterproof asphalt does not need to be used in conjunction with softening oil when applied to polymer-modified asphalt waterproof membrane.

[0035] The technical concept of the present invention is as follows:

[0036] The present invention uses asphalt and catalytic cracking oil slurry as basic raw materials to prepare waterproof asphalt, but FCC oil slurry contains a large amount of volatile components, which will release harmful smoke during the preparation and construction of waterproof membranes, which not only has an adverse effect on human health, but also accelerates the aging of waterproof membranes. Therefore, this problem is solved by introducing attapulgite-loaded copper oxide to modify 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide:

[0037] First, attapulgite is a silicate mineral with a unique layered chain structure. It has a good physical shielding effect on heat, oxygen and ultraviolet rays, and can improve the anti-aging performance of asphalt. However, attapulgite has poor compatibility with asphalt, is difficult to disperse evenly in asphalt, and is easy to settle. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is a substance with a phosphaphenanthrene structure. The reactive PH bond in its structure can react with the active light components in asphalt that are easily oxidized and volatilized at high temperatures to form stable derivatives, which can inhibit the volatilization of harmful gases in asphalt smoke. Under acidic conditions, the positively charged DOPO can exchange ions with the interlayer cations in attapulgite and enter the interlayer of attapulgite to obtain attapulgite-modified DOPO, which can improve the compatibility of attapulgite with asphalt and effectively improve the dispersion stability of attapulgite in asphalt. At the same time, the phosphaphenanthrene structure of DOPO also has good ultraviolet absorption ability, which can effectively improve the anti-photooxidation aging ability of asphalt.

[0038] Secondly, CuO was loaded on attapulgite-modified DOPO by the deposition-precipitation method to prepare loaded modified attapulgite-loaded CuO-modified DOPO. On the one hand, the oxygen vacancies provided by the surface defect structure of CuO were utilized to reduce the reaction activation energy of DOPO and the volatile components in asphalt. On the other hand, the high specific surface area of ​​attapulgite was used to improve the dispersion of copper oxide, promote the formation of CuO defect structure and the migration of oxygen holes, thereby improving the catalytic efficiency of CuO and significantly enhancing the smoke inhibition effect of attapulgite-modified DOPO on asphalt.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The present invention uses asphalt and catalytic cracking oil slurry as basic raw materials, and uses attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide as an anti-aging and environmentally friendly additive. The attapulgite-loaded CuO-modified DOPO has good dispersibility, excellent thermal stability, ultraviolet shielding and absorption effects, and excellent harmful smoke adsorption inhibition effects, which significantly improves the aging resistance and environmental protection of waterproof asphalt, can greatly reduce the emission of harmful gases in the production and construction process of waterproof membranes, and prolongs the service life of waterproof membranes. DETAILED DESCRIPTION

[0041] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0042] Example 1

[0043] The aging-resistant environmentally friendly waterproof asphalt in this embodiment includes the following raw materials by weight: 40 parts of asphalt, 60 parts of catalytic cracking oil slurry, and 1 part of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Among them, the asphalt is No. 70 road petroleum asphalt, with a softening point of 48.1°C and a needle penetration of 65dmm at 25°C; the catalytic cracking oil slurry has a freezing point of 18°C ​​and a density of 1.05g / cm 3 , the saturated content is 24% and the aromatic content is 59%.

[0044] The attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in this embodiment is prepared by the following method:

[0045] 1) adding attapulgite with a particle size of 250 mesh into 0.5 mol / L hydrochloric acid, the volume ratio of attapulgite mass to hydrochloric acid being 1 g:8 mL, stirring at a speed of 150 r / min for 20 min, filtering and separating the solid matter, drying at 110° C. for 1 h, and then grinding to obtain acid-treated attapulgite with a particle size of 250 mesh;

[0046] 2) 8 parts by mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 87 parts by mass of acid-treated attapulgite were added to anhydrous ethanol, the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous ethanol was 1 g:10 mL, the temperature was raised to 50° C. and stirred at a speed of 100 r / min for 60 min, after cooling to room temperature, the separated solid was filtered and dried at 110° C. for 2 h, and then ground to obtain attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a particle size of 250 mesh;

[0047] 3) Dissolve 5 parts by mass of copper nitrate in deionized water, the mass ratio of copper nitrate to deionized water is 1g:10mL, adjust the pH to 5.5 with a sodium hydroxide solution with a concentration of 1 mol / L, and then add all the attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide obtained in step 2), stir the reaction at a speed of 200r / min for 20min, filter and separate the solid, dry it at 110°C for 1h, and then grind it to obtain attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a particle size of 250 mesh.

[0048] The method for preparing the aging-resistant and environmentally friendly waterproof asphalt in this embodiment comprises the following steps:

[0049] The asphalt was heated to a molten state and then added into a modification tank. The temperature was raised to 140°C and then kept warm. Catalytic cracking oil slurry was first added and stirred at a speed of 300 r / min for 20 min. Then, attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added and stirred at a speed of 500 r / min for 40 min to obtain aging-resistant, environmentally friendly and waterproof asphalt.

[0050] Comparative Example 1-1

[0051] The only difference between Comparative Example 1-1 and Example 1 is that no attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added to the aging-resistant and environmentally friendly waterproof asphalt.

[0052] Comparative Example 1-2

[0053] The only difference between Comparative Example 1-2 and Example 1 is that in the aging-resistant and environmentally friendly waterproof asphalt, the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is replaced by attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0054] Comparative Examples 1-3

[0055] The only difference between Comparative Examples 1-3 and Example 1 is that in the aging-resistant and environmentally friendly waterproof asphalt, the copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide loaded with attapulgite is replaced by 0.5 parts of attapulgite and 0.5 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0056] Comparative Examples 1-4

[0057] The only difference between Comparative Examples 1-4 and Example 1 is that in the aging-resistant and environmentally friendly waterproof asphalt, the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is replaced by 0.9 parts of attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.1 parts of CuO.

[0058] Aging performance test:

[0059] The waterproof asphalt prepared in Example 1, Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4 were subjected to thin film oven aging (TFOT) (aging conditions: 163°C, 5h) and ultraviolet accelerated aging (UV) tests (aging conditions: ultraviolet light intensity 1200μW / cm 2 , 60℃, 9 days), the test conditions were the same, and then the softening point, needle penetration and low-temperature flexibility of the asphalt before and after aging were tested respectively, and the softening point increment, residual needle penetration ratio and low-temperature flexibility increment were calculated according to formula (1), formula (2) and formula (3). The results are shown in Table 1. The smaller the softening point increment and low-temperature flexibility increment before and after aging, the larger the residual needle penetration ratio, and the better the aging resistance of the asphalt.

[0060] Softening point increment = softening point after aging - softening point before aging (1)

[0061] Residual penetration ratio = (penetration after aging / penetration before aging) × 100% (2)

[0062] Low temperature flexibility increment = low temperature flexibility after aging - viscosity before aging (3)

[0063] Volatility test:

[0064] The H2S and VOCs contents in the volatiles of the waterproof asphalt prepared in Example 1, Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4 were tested respectively at a temperature of 180°C. The test method is as follows: 200g of waterproof asphalt was weighed, added to a 500mL three-necked flask, and heated to 180°C in a sealed manner. After heating for 60 minutes, the asphalt volatiles in the three-necked flask were extracted using a flue gas component detector (extraction time was 10s), and the H2S and VOCs contents in the volatiles were detected. The results are shown in Table 2.

[0065] Table 1

[0066]

[0067] Table 2

[0068]

[0069] The above results show that the softening point of the modified waterproof asphalt prepared in Example 1 is higher than that of Comparative Example 1-1, slightly lower than that of Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4, and the needle penetration is slightly lower than that of Comparative Example 1-1, higher than that of Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4. The low-temperature flexibility of the modified waterproof asphalt prepared in Example 1 and Comparative Example 1-1 is lower than that of Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4 (the lower the low-temperature flexibility stable temperature, the better the low-temperature performance); after TFOT and UV aging, the softening point increment and low-temperature flexibility increment of the modified asphalt prepared in Example 1 are significantly smaller than those of Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4, and the needle penetration retention rate is significantly higher than that of Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4. This shows that the waterproof asphalt prepared by using attapulgite loaded CuO to modify DOPO has excellent high and low temperature performance and resistance to thermal oxidation and ultraviolet aging.

[0070] As can be seen from Table 2, after heating at 180°C for 60 minutes, the H2S content in the volatiles of Comparative Example 1-1 exceeds 200ppm, and the VOCs content is 1998ppm, the H2S content in the volatiles of attapulgite-modified DOPO-modified waterproof asphalt is 182ppm, and the VOCs content is 1002ppm, the H2S content in the volatiles of DOPO / attapulgite-modified waterproof asphalt is 191ppm, and the VOCs content is 1352ppm, the H2S content in the volatiles of CuO / attapulgite-modified DOPO-modified waterproof asphalt is 185ppm, and the VOCs content is 113 2ppm, while the H2S content and VOCs content in the volatiles of the waterproof asphalt modified with DOPO modified by attapulgite loaded with CuO are significantly lower than those in the volatiles of Comparative Example 1-1, Comparative Example 1-2, Comparative Example 1-3 and Comparative Example 1-4, the H2S content in its volatiles is 78ppm, and the VOCs content is 267ppm, which indicates that DOPO modified with attapulgite can reduce the H2S content and VOCs content in the volatiles of waterproof asphalt, and CuO can significantly improve the inhibitory effect of DOPO modified with attapulgite on the volatiles of waterproof asphalt, and the prepared waterproof asphalt has better environmental protection.

[0071] Example 2

[0072] The aging-resistant environmentally friendly waterproof asphalt in this embodiment includes the following raw materials by weight: 50 parts of asphalt, 50 parts of catalytic cracking oil slurry, and 2 parts of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide. Among them, the asphalt is No. 70 road petroleum asphalt, with a softening point of 45.6°C and a needle penetration of 78dmm at 25°C; the catalytic cracking oil slurry has a freezing point of 22°C and a density of 1.07g / cm 3, the saturated content is 21% and the aromatic content is 63%.

[0073] The attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in this embodiment is prepared by the following method:

[0074] 1) adding attapulgite with a particle size of 800 mesh into 1 mol / L hydrochloric acid, the volume ratio of attapulgite mass to hydrochloric acid is 1 g:5 mL, stirring at a speed of 200 r / min for 30 min, filtering and separating the solid matter, drying at 105° C. for 2 h, and then grinding to obtain acid-treated attapulgite with a particle size of 800 mesh;

[0075] 2) adding 10 parts by mass of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 82 parts by mass of acid-treated attapulgite to anhydrous ethanol, the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous ethanol is 1 g:8 mL, heating to 60° C. and stirring at 200 r / min for 30 min, cooling to room temperature, filtering and separating the solid, drying at 105° C. for 2 h, and then grinding to obtain attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a particle size of 800 mesh;

[0076] 3) 8 parts by mass of copper nitrate were dissolved in deionized water, the mass ratio of copper nitrate to deionized water was 1 g: 15 mL, the pH was adjusted to 5 with a sodium hydroxide solution having a concentration of 0.5 mol / L, and then all the attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide obtained in step 2) was added, and the reaction was stirred at a speed of 150 r / min for 30 min. The solid separated by filtration was dried at 105 ° C for 2 h, and then ground to obtain attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide with a particle size of 800 mesh.

[0077] The method for preparing the aging-resistant and environmentally friendly waterproof asphalt in this embodiment comprises the following steps:

[0078] The asphalt was heated to a molten state and then added into a modification tank. The temperature was raised to 130°C and then kept warm. Catalytic cracking oil slurry was first added and stirred at a speed of 400 r / min for 15 min. Then, attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added and stirred at a speed of 400 r / min for 50 min to obtain aging-resistant, environmentally friendly and waterproof asphalt.

[0079] Comparative Example 2-1

[0080] The only difference between Comparative Example 2-1 and Example 2 is that the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is not added to the aging-resistant and environmentally friendly waterproof asphalt.

[0081] Comparative Example 2-2

[0082] The only difference between Comparative Example 2-2 and Example 2 is that in the aging-resistant and environmentally friendly waterproof asphalt, the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is replaced by attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0083] Comparative Examples 2-3

[0084] The only difference between Comparative Example 2-3 and Example 2 is that in the aging-resistant and environmentally friendly waterproof asphalt, the copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide loaded with attapulgite is replaced by 1 part of attapulgite and 1 part of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0085] Comparative Examples 2-4

[0086] The only difference between Comparative Example 2-4 and Example 2 is that in the aging-resistant and environmentally friendly waterproof asphalt, the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is replaced by 1.5 parts of attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 0.5 parts of CuO.

[0087] The waterproof asphalt prepared in Example 2, Comparative Example 2-1, Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4 were respectively subjected to aging performance test and volatility test. The results are shown in Table 3 and Table 4.

[0088] Table 3

[0089]

[0090] Table 4

[0091]

[0092] The above results show that the softening point of the attapulgite-loaded CuO-modified DOPO-modified waterproof asphalt prepared in Example 2 is slightly higher than that of Comparative Example 2-1, and lower than that of Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4, and the needle penetration is slightly lower than that of Comparative Example 2-1, and higher than that of Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4. The low-temperature flexibility of the modified waterproof asphalt prepared in Example 2 and Comparative Example 2-1 is lower than that of Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4; after TFOT and UV aging, the softening point increment and low-temperature flexibility increment of the attapulgite-loaded CuO-modified DOPO-modified waterproof asphalt prepared in Example 2 are both smaller than those of Comparative Example 2-1, Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4, and the needle penetration retention rate is higher than that of Comparative Example 2-1, Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4, indicating that the waterproof asphalt prepared by using attapulgite-loaded CuO-modified DOPO has excellent high and low temperature properties as well as heat oxygen and UV aging resistance.

[0093] As can be seen from Table 4, after heating at 180°C for 60 minutes, the H2S content in the volatiles of Comparative Example 2-1 exceeds 200ppm, and the VOCs content is 1847ppm, the H2S content in the volatiles of attapulgite-modified DOPO-modified waterproof asphalt is 159ppm, and the VOCs content is 672ppm, the H2S content in the volatiles of DOPO / attapulgite-modified waterproof asphalt is 165ppm, and the VOCs content is 885ppm, the H2S content in the volatiles of CuO / attapulgite-modified DOPO-modified waterproof asphalt is 160ppm, and the VOCs content is 164ppm. The VOCs content is 782ppm, while the H2S content and VOCs content in the volatiles of the waterproof asphalt modified by DOPO modified by attapulgite loaded with CuO are significantly lower than those in Comparative Example 2-1, Comparative Example 2-2, Comparative Example 2-3 and Comparative Example 2-4, in which the H2S content in the volatiles is 45ppm and the VOCs content is 179ppm. This also shows that DOPO modified by attapulgite loaded with CuO significantly reduces the volatility of harmful components in waterproof asphalt, and the more the amount of DOPO modified by attapulgite loaded with CuO is added, the better the inhibition effect is.

[0094] Application Examples

[0095] The aging-resistant and environmentally friendly waterproof asphalt described in the present invention is the basic raw material of the polymer modified asphalt waterproof membrane. In order to more specifically illustrate the effect of the invention, a polymer modified asphalt waterproof membrane is listed here, and its components and the weight proportions are: 48 to 55 parts of waterproof asphalt, 3 to 5 parts of styrene-butadiene-styrene block copolymer (SBS), 3 to 5 parts of polypropylene (PP), 10 to 15 parts of rubber powder, and 25 to 35 parts of filler.

[0096] The aging-resistant and environmentally friendly waterproof asphalt prepared in each embodiment and each comparative example is used to prepare a polymer-modified asphalt waterproof roll. The components of the polymer-modified asphalt waterproof roll include: 50 parts of waterproof asphalt, 4 parts of SBS, 4 parts of PP, 12 parts of rubber powder, and 30 parts of filler. The specific preparation process is as follows:

[0097] a) Weigh a measured amount of waterproof asphalt and put it into the modification tank, control the temperature at 140±5℃, and stir at 500r / min for 10min;

[0098] b) Add measured amount of SBS to a, adjust the temperature to 180±5°C, and stir at 1800r / min for 60min;

[0099] c) Add measured portions of PP and rubber powder to part b, adjust the temperature to 180±5°C, and stir at 1800r / min for 90min;

[0100] d) Add a measured amount of filler to c, adjust the temperature to 190±5°C, and stir at 1000 r / min for 90 min;

[0101] e) Apply d to both sides of the polyester base, control the single-side thickness to 1.5 mm, and cover the upper and lower surfaces with polyethylene isolation films to obtain a polymer-modified asphalt waterproof membrane.

[0102] The polymer modified asphalt waterproofing membrane prepared by the aging-resistant and environmentally friendly waterproof asphalt in each embodiment and each comparative example was subjected to a heat aging test, and the test conditions were: 80°C, 10 days, and then the softening point, low-temperature flexibility and joint peeling strength of the coating material before and after aging were tested respectively, and the softening point increment, low-temperature flexibility change and joint peeling strength retention rate were calculated according to formula (4), formula (5) and formula (6), and the results are shown in Table 5. The smaller the softening point increment and low-temperature flexibility change before and after aging, the higher the peeling strength retention rate, and the better the aging resistance of the waterproofing membrane.

[0103] Softening point increment = softening point after aging - softening point before aging (4)

[0104] Change in low temperature flexibility = low temperature flexibility after aging - low temperature flexibility before aging (5)

[0105] Peel strength retention rate = peel strength after aging / peel strength before aging × 100% (6)

[0106] Table 5

[0107] Experimental Group Softening point increment / ℃ Low temperature flexibility change / ℃ Seam peel strength retention rate / % Example 1 3.1 3 82.1 Comparative Example 1-1 6.3 7 68.5 Comparative Example 1-2 4.5 5 71.3 Comparative Examples 1-3 5.2 6 70.2 Comparative Examples 1-4 4.1 5 72.8 Example 2 2.5 2 85.2 Comparative Example 2-1 7.5 7 67.2 Comparative Example 2-2 4.9 4 76.8 Comparative Examples 2-3 5.8 5 73.3 Comparative Examples 2-4 4.0 4 77.5

[0108] It can be seen from Table 5 that compared with the comparative example, the embodiment has a lower softening point increment and low-temperature flexibility change after aging, and a higher joint peel strength retention rate, which indicates that the waterproof membrane prepared by adding attapulgite-loaded CuO-modified DOPO waterproof asphalt has better anti-aging performance.

[0109] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. An aging-resistant and environmentally friendly waterproof asphalt, characterized in that: The method comprises the following raw materials in parts by weight: 30-60 parts of asphalt, 40-70 parts of catalytic cracking oil slurry, and 0.5-2.5 parts of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

2. The aging-resistant and environmentally friendly waterproof asphalt according to claim 1 is characterized in that: The preparation method of attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide comprises the following steps: 1) adding attapulgite to hydrochloric acid, stirring and drying the obtained solid to obtain acid-treated attapulgite; 2) adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and acid-treated attapulgite into anhydrous ethanol, heating and stirring to react, and drying the obtained solid to obtain attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide; 3) After copper nitrate is dissolved in water, the pH is adjusted with a sodium hydroxide solution, and then attapulgite-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added, and after stirring for reaction, the obtained solid is dried to obtain attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

3. The aging-resistant and environmentally friendly waterproof asphalt according to claim 2 is characterized in that: In step 2) and step 3), the weight proportions of the raw materials are: 5 to 20 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 70 to 90 parts of acid-treated attapulgite, and 5 to 10 parts of copper nitrate.

4. The aging-resistant and environmentally friendly waterproof asphalt according to claim 2 is characterized in that: In step 2), the mass ratio of the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous ethanol is 1 g: (8-10) mL; the stirring speed of the heated stirring reaction is 100-300 r / min, the reaction temperature is 50-60° C., and the reaction time is 30-60 min.

5. The aging-resistant and environmentally friendly waterproof asphalt according to claim 2 is characterized in that: In step 3), the mass ratio of copper nitrate to water is 1 g: (10-20) mL; the concentration of the sodium hydroxide solution is 0.5-1 mol / L, and the pH is adjusted to 5-5.5; the stirring speed of the stirring reaction is 100-300 r / min, and the reaction time is 20-30 min.

6. The aging-resistant and environmentally friendly waterproof asphalt according to claim 2 is characterized in that: In step 1), the particle size of the attapulgite is 200-1000 mesh, the concentration of the hydrochloric acid is 0.5-1 mol / L, the volume ratio of the mass of the attapulgite to the hydrochloric acid is 1 g: (5-10) mL; the stirring speed of the stirring treatment is 100-200 r / min, and the treatment time is 10-30 min.

7. The aging-resistant and environmentally friendly waterproof asphalt according to claim 1 is characterized in that: The asphalt is road petroleum asphalt, with a softening point of 45-50°C and a needle penetration of 60-80 dmm at 25°C; the catalytic cracking slurry is the base oil produced in the production process of the heavy oil catalytic cracking unit, with a solidification point of 15-25°C and a density of 1.03-1.07 g / cm 3 The saturated content is 20-30%, and the aromatic content is 50-65%; the particle size of the attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 200-1000 meshes.

8. A method for preparing the aging-resistant and environmentally friendly waterproof asphalt according to any one of claims 1 to 7, characterized in that: The following steps are involved: The asphalt is heated to a molten state and then added to a modification tank. The temperature is raised to a preset temperature and then kept warm. Catalytic cracking oil slurry is first added for stirring once, and then attapulgite-loaded copper oxide-modified 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is added and stirred for a second time to obtain aging-resistant, environmentally friendly and waterproof asphalt.

9. The method for preparing aging-resistant and environmentally friendly waterproof asphalt according to claim 8, characterized in that: The preset temperature is 120-150° C.; the stirring rate of the first stirring is 300-500 r / min, and the stirring time is 15-20 min; the stirring rate of the second stirring is 300-500 r / min, and the stirring time is 30-60 min.

10. Use of the aging-resistant and environmentally friendly waterproof asphalt according to any one of claims 1 to 7 in polymer-modified asphalt waterproof membrane.

Citation Information

Patent Citations

  • Preparation method of silver-copper oxide composite material

    CN107552069A

  • Preparation method of copper oxide clay and application

    CN108607557A

  • Preparation method of attapulgite-loaded transitional metal oxide composite material and application thereof

    CN109225206A

  • Low-carbon-emission modified asphalt

    CN113604065A

  • Environment-friendly waterproof asphalt and preparation method thereof

    CN113773659A